Titanium Application Increases Phosphorus Uptake Through Changes in Auxin Content and Root Architecture in Soybean (Glycine Max L.) - Hussain, Sajad; Shafiq, Iram; Skalicky, Milan; Brestic, Marian; Rastogi, Anshu; Mumtaz, Maryam; Hussain, Muzammil; Iqbal, Nasir; Raza, Muhammad Ali; Manzoor, Sumaira; Liu, Weiguo; Yang, Wenyu (Frontiers in Plant Science, 2021)
Phosphorus (P) is an essential macronutrient needed for plant growth, development, and production. A deficiency of P causes a severe impact on plant development and productivity. Several P-based fertilizers are being used in agriculture but limited uptake of P by the plant is still a challenge to be solved. Titanium (Ti) application increases the nutrient uptake by affecting the root growth; however, the role of Ti in plant biology, specifically its application under low light and phosphorus stress, has never been reported. Therefore, a pot study was planned with foliar application of Ti (in a different concentration ranging from 0 to 1,000 mg L–1) under different light and P concentrations. The result indicated that under shade and low P conditions the foliar application of Ti in different concentrations significantly improves the plant growth parameters such as root length, root surface area, root dry matter, and shoot dry matters. The increase was observed to be more than 100% in shade and low P stressed soybean root parameter with 500 mg L–1 of Ti treatment. Ti was observed to improve the plant growth both in high P and low P exposed plants, but the improvement was more obvious in Low P exposed plants. Auxin concentration in stressed and healthy plant roots was observed to be slightly increased with Ti application. Ti application was also observed to decrease rhizosphere soil pH and boosted the antioxidant enzymatic activities with an enhancement in photosynthetic efficiency of soybean plants under shade and P stress. With 500 mg L–1 of Ti treatment, the photosynthetic rate was observed to improve by 45% under shade and P stressed soybean plants. Thus, this work for the first time indicates a good potential of Ti application in the low light and P deficient agricultural fields for the purpose to improve plant growth and development parameters.